New Pieza Evenhuis (Diptera, Mythicomyiidae, Mythicomyiinae) from Northeast Brazil - Mendes, Luanna L.; Lamas, Carlos J.e.; Evenhuis, Neal L.; Limeira-De-Oliveira, Francisco (Zootaxa, 2019)
The genus Pieza Evenhuis, 2002 has 11 known species but only one recorded from Brazil. In this paper, eight new species, P. ankh sp. nov., P. aurislepus sp. nov., P. bittencourti sp. nov., P. parakake sp. nov., P. parnasecon sp. nov., P. rafaeli sp. nov., P. silvanae sp. nov. and P. yeatesi sp. nov., are described from Maranhão and Piauí in the Northeast of Brazil. A key to genera of Mythicomyiinae of the world (modified from Rafael and Limeira-de-Oliveira 2014) and the Brazilian species of Pieza is provided. In addition, a distribution map for the Brazilian species of Pieza is presented.